2016
DOI: 10.1111/ajt.13542
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ST2 Distinguishes Incidences of Pediatric Heart and Small Bowel Transplant Rejection

Abstract: Elevated serum soluble (s) Suppressor of Tumorigenicity 2 (ST2) is observed during cardiovascular and inflammatory bowel diseases. To ascertain whether modulated ST2 levels signify heart (HTx) or small bowel transplant (SBTx) rejection, we quantified sST2 in serially obtained pediatric HTx (n=41) and SBTx recipient (n=18) sera. At times of biopsy-diagnosed HTx rejection (cellular and/or antibody-mediated), serum sST2 was elevated compared to rejection-free time points (1714±329 vs. 546.5±141.6 pg/ml; P=0.0002)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
(72 reference statements)
0
31
0
Order By: Relevance
“…The role of sST2 as a biomarker to predict acute rejection after HTx has been investigated previously 16)17). Pascual-Figal et al16) reported that sST2 levels were increased as compared with the pre-rejection period, and decreased again after treatment of acute rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of sST2 as a biomarker to predict acute rejection after HTx has been investigated previously 16)17). Pascual-Figal et al16) reported that sST2 levels were increased as compared with the pre-rejection period, and decreased again after treatment of acute rejection.…”
Section: Discussionmentioning
confidence: 99%
“…However, correcting for confounding factors of the time after HTx, a statistical difference was not found. More recently, Mathews et al reported that a higher level of sST2 (>600 pg/mL) could discriminate graft rejection with an area under the curve of 0.72±0.05 in pediatric HTx patients 17). However, they had higher rates of rejection events, and included a large proportion of acute humoral rejection among the significant rejection group.…”
Section: Discussionmentioning
confidence: 99%
“…ST2 and sST2 are induced or augmented in leukocytes and stromal cells by pro-inflammatory cytokines, TLR ligands, and mechanical stress. Building upon our early rodent studies that established that ST2 is increased locally, but not systemically during rejection of heterotopic heart transplants (26), we showed that the alloimmune-associated pro-inflammatory cytokines increase graft ST2 during rejection episodes in pediatric SOTx recipients (73). Graft ST2 increases were reflected in increased serum sST2 levels that signified rejection in cohorts of small bowel or heart transplant recipients (73).…”
Section: Alarmins and Their Receptors As Diagnostic And Prognostic Bimentioning
confidence: 93%
“…Building upon our early rodent studies that established that ST2 is increased locally, but not systemically during rejection of heterotopic heart transplants (26), we showed that the alloimmune-associated pro-inflammatory cytokines increase graft ST2 during rejection episodes in pediatric SOTx recipients (73). Graft ST2 increases were reflected in increased serum sST2 levels that signified rejection in cohorts of small bowel or heart transplant recipients (73). Similarly, high serum sST2 acts as a reliable biomarker predicting resistance in GVHD patients to corticosteroid therapy and non-relapse mortality (74).…”
Section: Alarmins and Their Receptors As Diagnostic And Prognostic Bimentioning
confidence: 93%
“…IL-33 can induce direct effects in ST2 + Tregs but also indirect effects via IL-33-responsive DCs (110). Interestingly, elevated levels of sST2 in plasma are observed during episodes of acute cardiac and small bowel allograft rejection in patients, suggesting that IL-33/ST2 signaling might be dysregulated in human transplantation (111,112).…”
Section: Il-33 and Organ Rejectionmentioning
confidence: 99%